Answer:
pretty sure it's 15 but if you used my answer and it was wrong srr
Answer:
<u>-1 and -5</u>
Step-by-step explanation:
m^2 + 6m + 5 = 0 is factored to: (m + 1)(m + 5) = 0.
The zero product property states that one of the represented parenthesis must equal zero to satisfy the right side of the equation.
(m + 1) = 0
(-1 + 1) = 0
This means that one of the values for m is -1.
(m + 5) = 0
(-5 + 5) = 0
This means that one of the values for m is -5.
<u>Moreover, the value of m by factoring is -1 and -5</u>
Answer: The answer would be choice C because there is a constant rate of change of 3 :)
Step-by-step explanation:
follow order of operations:
3+16/4 = 3+4 = 7
Answer:
by experts to help you in doubt clearance & scoring excellent marks in exams.
Step-by-step explanation: